Meningkatkan Kemampuan Problem Solving Siswa Kelas V SDN Sukarindik Menggunakan Media Puzzle Pada Materi Pecahan Campuran - Rahmi Nur Syabani; Riza Fatimah Zahrah; Winarti Dwi Febriani (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Problem solving ability is one of the important skills in mathematics learning, especially in solving story problems on mixed fractions. The results of initial observations in grade V of SDN Sukarindik showed that students' problem solving abilities were still low, with only 33.33% of students achieving the Minimum Completion Criteria (KKM). This study aims to improve students' problem solving abilities through the use of fraction puzzle media in mathematics learning. The method used was the Classroom Action Research (CAR) model of Kemmis and McTaggart which was implemented in two cycles. Data collection instruments were tests, observations, and documentation. The results of the study showed a significant increase. The average student score increased by 36.91 points, namely from 46.42 (very poor category) in the initial ability test stage to 83.33 (good category) in cycle II. Learning completeness also increased by 57.14%, from 33.33% (very poor category) to 90.47% (very good category). Student activity in learning increased by 8%, from 80% to 88% (very good category). Teachers' ability in lesson planning also showed a 2.18% increase, from 96.73% to 98.91% (very good category). Thus, the use of puzzles has been proven to improve students' problem-solving skills in mixed fractions, as well as creating active, meaningful, and well-planned learning.